Ecumenical reflections on race, racism, and whiteness in the afterlife of apartheid in South Africa - van Wyngaard, Cobus; van der Riet, Louis (Stellenbosch Theological Journal, 2025)
This article examines the contributions made to a 28 April 2022 ecumenical dialogue on race, racism, and whiteness in South Africa. Following a careful analysis of the recordings and transcripts from this dialogue the article identifies multiple themes regarding race and whiteness that emerged from participants at this event. The article seeks to point out contemporary challenges identified by Christian leaders around race and whiteness in order to outline potential challenges both in terms of ecclesial actions on anti-racism but more specifically key research agenda to critically accompany faith communities responding to questions around race, racism, and whiteness. The article concludes by suggesting that there is a clear need to revisit the possible place of churches in responding to the unfinished work of the TRC, to focus specific attention on the intersection of congregational studies and anti-racism, in order to develop congregational practices that will contribute to the ongoing dismantling of structural racism, and further theological research needed to look into the ways in which South African theology was, and continues to be, formed by a colonial and white imagination, and what a faith and theology liberated from its colonial shackles would look like.